Antecedents to teachers’ perceptions of the usefulness of ICTs for business education classroom instructions in Nigerian tertiary institutions - Isiyaku, Dauda Dansarki; Mohd Ayub, Ahmad Fauzi; Abdul Kadir, Suhaida (Springer Netherlands, 2018)
This study investigated the antecedents to Nigerian business education teachers’ perceptions of the usefulness of technology in the classroom. Theoretical support for the study was based on the work of Venkatesh and Bala’s (Decis Sci 39(2):273–315, 2008) Technology Acceptance Model III where computer self-efficacy and perceived enjoyment were identified as antecedents to perceived ease of use of technology while subjective norm was identified as an antecedent to perceived usefulness. The study proposed a structural model to investigate whether computer self-efficacy, perceived enjoyment, and subjective norm were antecedents to teachers’ perceived usefulness of ICTs in Business Education classrooms of Nigerian tertiary institutions. The study was a survey research involving 212 teachers sampled from the Business Education faculties of 13 tertiary colleges in Northwestern Nigeria, sub-Sahara Africa. The research instrument for data collection was a structured questionnaire using items adapted from previously validated studies. The questionnaire yielded high-reliability coefficients both at the pilot and actual study stages. SPSS version 22 was used for descriptive statistics analyses, and AMOS 22 was used for structural equation modeling. The study model explained about 33% of the variance in teachers’ perceptions of the usefulness of ICTs in the classroom. Two of the hypotheses of the study were statistically significant. Teachers’ computer self-efficacy and perceived enjoyment of ICTs were found to significantly influence their perceived usefulness of ICTs. The study recommends that Nigerian teachers should be trained to integrate ICTs in the curriculum and be provided with ICT support services in order to help them with ICT difficulties in the classroom.